2021
DOI: 10.1039/d1cb00056j
|View full text |Cite
|
Sign up to set email alerts
|

Discovery, X-ray structure and CPP-conjugation enabled uptake of p53/MDM2 macrocyclic peptide inhibitors

Abstract: Mouse double minute 2 homolog (MDM2, Hdm2) is an important negative regulator of the tumor suppressor p53. Using a mRNA based display technique to screen a library of >1012 in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…To identify peptides that bind to human TEAD4 (region 217–434), we used the RNA-display technology (10 12 in-vitro translated macrocyclic peptides) as previously described . The mRNA display screening revealed a macrocyclic hit series with several strongly enriched analogues (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…To identify peptides that bind to human TEAD4 (region 217–434), we used the RNA-display technology (10 12 in-vitro translated macrocyclic peptides) as previously described . The mRNA display screening revealed a macrocyclic hit series with several strongly enriched analogues (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…The 2‐position of the indole ring is oxidized to a carbonyl group; the 3‐position is a spiro atom, and the substituted pyrrole ring shares the same carbon atom; the 7‐position of the indole ring is often substituted (usually chlorinated). X ‐ray diffraction analysis shows that the indole ring or the structure similar to the indole ring has a good combination with the active cavity of Trp23, and the substituted tetrahydropyrrole ring has a hydrophobic effect with the active cavity of Phe19 and Leu26 [38] . The effects of spiroepoxyindole compounds are more significant.…”
Section: Substituted Indole P53‐mdm2 Inhibitorsmentioning
confidence: 99%
“…In addition, the research data in vivo also showed that spirooxyindole compounds were active compounds with excellent pharmaceutical properties for oral use. In particular, APG‐115 has a very high affinity for MDM2 (Ki<1 nM), strong cell activity and good oral pharmacokinetic characteristics, and can achieve complete and lasting tumor regression in vivo [38] …”
Section: Substituted Indole P53‐mdm2 Inhibitorsmentioning
confidence: 99%
See 2 more Smart Citations